Aromatic monomers generation by Aspergillus and penicillium spp from residual wheat straw lignin - Baltierra Trejo, Eduardo; Márquez-Benavides, Liliana; Hernández-Berriel, Ma. del Consuelo; Sánchez-Yáñez, Juan Manuel (Vitae, 2016)
Background: Wheat straw is an agricultural waste, which contains 17% of lignin, a recalcitrant polymer with biotechnological potential provided it is depolymerized. Lignin depolymerization has attracted interest because it yields aromatics of industrial interest; chemical and physical methods are available but entail economic and environmental constraints. An alternative is to exploit the ligninolytic capacity of mitosporic fungi, such as Aspergillus and Penicillium spp. There are few reports on the use of these funguses in the generation of aromatics by lignin depolymerization. Objetives: To use Aspergillus and Penicillium spp in the biological generation of aromatics from semipurified residual wheat straw lignin. Methods: Funguses were grown in semipurified residual wheat straw lignin for 28 days; produced aromatics were followed using gas chromatography. Results: Obtained results indicate a range of aromatics produced, i.e. 3,5 mg mL-1 guaiacol, 3,3 vanillin, 3,2 hydroxybenzoic acid, 3,3 vanillinic, 10,1 syringic and 21,9 ferulic. Conclusions: Aspergillus and Penicillium represent an ecological option in the exploit of semi-purified residual lignin from wheat straw to generate aromatics in a shorter period from an abundant and cheap residue.